Trust-enabled drivers of Gen Z consumers’ willingness to pay for sustainable packaging: an extended TRUST-PACT model - D. Y., Ashwini; Moodbidri, Sudhir (Frontiers in Sustainability, 2026)
IntroductionSustainable packaging has become a key element of corporate sustainability strategies amid growing concerns about plastic waste, resource depletion, and environmental transparency. Generation Z consumers play a crucial role in this transition due to their strong environmental awareness and influence on market demand. However, despite positive pro-environmental attitudes, Gen Z consumers often hesitate to pay a price premium for sustainable packaging, revealing an attitude–behavior gap. Existing consumer behavior models inadequately explain this gap, particularly in contexts of information asymmetry and greenwashing. This study addresses this limitation by integrating trust-based mechanisms into a unified behavioral framework.MethodsA quantitative research design was employed using survey data collected from 120 Generation Z consumers in India. Constructs were measured using validated Likert-scale items. The proposed TRUST-PACT (Trust-Enabled Perceived Authenticity and Communicative Transparency) framework was tested using Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine direct, mediating, and moderating relationships among environmental awareness, perceived benefits, green values, brand trust, eco-label credibility, communication transparency, greenwashing risk, social influence, and price sensitivity.ResultsThe findings indicate that environmental awareness, perceived benefits, and green values significantly influence willingness to pay for sustainable packaging primarily through brand trust, which emerges as a strong partial mediator. Eco-label credibility and communication transparency strengthen the trust–willingness-to-pay relationship, while perceived greenwashing risk weakens it. Social influence enhances the translation of environmental awareness into trust, whereas price sensitivity constrains premium acceptance despite favorable evaluations.DiscussionThe study demonstrates that willingness to pay for sustainable packaging among Generation Z is not driven by attitudes alone but by trust formed under credible and transparent communication conditions. The TRUST-PACT framework offers a parsimonious, trust-centered explanation of sustainable purchasing behavior in digitally mediated markets. The findings provide practical implications for marketers and policymakers by highlighting the need for verifiable eco-labels, transparent digital disclosures, and strategies to reduce greenwashing perceptions.